Makna Denotatif dan Konotatif pada Lirik Lagu “Saudade” Karya Kunto Aji - Dina Nopita; Desma Yuliadi Saputra; Rina Andriani (Asosiasi Riset Ilmu Pendidikan Indonesia, 2026)
This study aims to describe the denotative and connotative meanings in the lyrics of Kunto Aji's song